2022
DOI: 10.3389/fendo.2022.1001349
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative metabolic analysis of orbital adipose/connective tissue in patients with thyroid-associated ophthalmopathy

Abstract: ObjectiveThyroid-associated ophthalmopathy (TAO) is a disfiguring autoimmune disease, which destroys the structure of orbital tissues and even threatens vision. Metabolic reprograming is critical in autoimmune diseases; however, the metabolic basis of TAO remains to be clarified. Our study aimed to reveal the metabolic profile of TAO.MethodsOrbital adipose/connective tissues from eleven TAO patients and twelve control subjects were collected during surgeries and analyzed with liquid chromatograph-mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It has been reported that the inflammatory levels significantly upregulated in the adipose tissue and muscle of TAO patients ( Carroll et al, 2013 ; Natesha et al, 1992 ; Khong et al, 2015 ). Huang et al (2022) demonstrated that endoplasmic reticulum stress initiated by cholesterol metabolism may provoke adipose inflammation in TAO. Adipocyte-derived CP and AGT play a critical role in adipogenesis as well as inflammation ( Carroll et al, 2013 ; Bednarek, Wysocki & Sowinski, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the inflammatory levels significantly upregulated in the adipose tissue and muscle of TAO patients ( Carroll et al, 2013 ; Natesha et al, 1992 ; Khong et al, 2015 ). Huang et al (2022) demonstrated that endoplasmic reticulum stress initiated by cholesterol metabolism may provoke adipose inflammation in TAO. Adipocyte-derived CP and AGT play a critical role in adipogenesis as well as inflammation ( Carroll et al, 2013 ; Bednarek, Wysocki & Sowinski, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…By selecting control samples from the same location as the TED patients, we gained a comparative advantage. Recent literature reports have highlighted the structural, pathophysiological, metabolic, and molecular differences that exist in adipose tissue from different anatomical sites (40,41). In contrast to previous studies on orbital adipose tissue, where control samples were obtained from non-retrobulbar adipose tissue in patients undergoing plastic surgery around the eyes, nose, and ears, which differs from the retrobulbar adipose tissue of TED patients (41), our choice of controls provided a more comparable location.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reports have highlighted the structural, pathophysiological, metabolic, and molecular differences that exist in adipose tissue from different anatomical sites (40,41). In contrast to previous studies on orbital adipose tissue, where control samples were obtained from non-retrobulbar adipose tissue in patients undergoing plastic surgery around the eyes, nose, and ears, which differs from the retrobulbar adipose tissue of TED patients (41), our choice of controls provided a more comparable location. For instance, Zhang, et al reported that OATs had higher expression of Iroquois homeobox-family (IRX-3&5) and lower expression in HOX-family/TBX5 compared to white adipose tissue/brown adipose tissue/brown in white adipose tissue development (13).…”
Section: Discussionmentioning
confidence: 99%
“…In orbital tissues from GO patients, Huang et al revealed that ER stress-related gene (ATF6, PERK, and IRE1α) expression was higher than in control orbital tissues [ 51 ]. Further study showed that silencing PERK could reduce oxidative stress and adipogenesis in the GO orbital fibroblasts [ 52 ].…”
Section: Endoplasmic Reticulum (Er) Stress In the Ecm Of Gomentioning
confidence: 99%